Learning DevSecOps a practical guide to processes and tools - Suehring, Steve (Ascent Audio, 2024)
How do some organizations maintain 24-7 internet-scale operations? How can organizations integrate security while deploying new features? How do organizations increase security within their DevOps processes? This practical guide helps you answer those questions. Steve Suehring provides unique content to help practitioners and leadership successfully implement DevOps and DevSecOps. Learning DevSecOps emphasizes prerequisites that lead to success through best practices and then takes you through some of the tools and software used by successful DevSecOps-enabled organizations. You'll learn how DevOps and DevSecOps can eliminate the walls that stand between development, operations, and security so that you can tackle the needs of other teams.